1996
DOI: 10.1093/oxfordjournals.ndt.a027024
|View full text |Cite
|
Sign up to set email alerts
|

Complement depletion during haemofiltration with polyacrilonitrile membranes

Abstract: Background. Polyacrylonitrile (PAN, AN69®) dialysis membranes have been shown to improve the outcome of critically ill patients. Factor D is an essential enzyme of the alternative pathway of complement and is increased during renal failure. On the other hand the contact of blood with biomaterials activates the complement cascade through the alternative pathway. PAN niters adsorb factor D which looses its enzymatic activity whilst bound to the membrane [1]; the complement alternative pathway function of serum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 6 publications
3
17
0
2
Order By: Relevance
“…Gasche et al performed CVVH using an AN69 membrane hemofilter (AN69-CVVH) in seven patients and reported removal of factor D (activating complement) by adsorption [36]. De Vriese et al performed AN69-CVVH in 15 patients with septic AKI and reported a rapid decrease in blood cytokine levels and improvement in cardiac output, pulmonary artery wedge pressure, and systemic vascular resistance [37].…”
Section: Pmma Hemofiltermentioning
confidence: 99%
“…Gasche et al performed CVVH using an AN69 membrane hemofilter (AN69-CVVH) in seven patients and reported removal of factor D (activating complement) by adsorption [36]. De Vriese et al performed AN69-CVVH in 15 patients with septic AKI and reported a rapid decrease in blood cytokine levels and improvement in cardiac output, pulmonary artery wedge pressure, and systemic vascular resistance [37].…”
Section: Pmma Hemofiltermentioning
confidence: 99%
“…58] have shown that synthetic filters in common use in hemofiltration can extract nearly every substance involved in sepsis to a certain degree. Prominent examples are complement factors [59,60], TNF, IL-1, IL-6 [60][61][62][63], IL-8 [64] and platelet-activating factor [65,66]. Regarding plasma cytokine levels, their decrease appeared nevertheless of minor degree.…”
Section: Crrtmentioning
confidence: 99%
“…From several animal and human investigations we know that our ability to remove middle molecules (especially those 15,000 in molecular weight such as cytokines and complement components) is limited when using current technology [13]. Convective extraction is probably better than diffusive removal, but still small in amount and unlikely to have a biological or clinical impact [14].…”
Section: What Can Current Extracorporeal Blood Purification Therapiesmentioning
confidence: 99%